Pascal's Pyramid

Imagine a pyramid made out of blocks, where the first layer has 1 block, the second layer is a 2 × 2 2\times 2 square made up of 4 blocks, the third layer is a 3 × 3 3\times 3 square made up of 9 blocks, and so on, so that each n th n^\text{th} layer is a square made from n 2 n^2 blocks.

Each block has a number written on it. The top block has the number 1 written on it, but every other block has the sum of all the blocks that touch its top side written on it. The first five layers are as follows:

What number would be written on the block that is in the 3 rd 3^\text{rd} column and 4 th 4^\text{th} row of the 10 0 th 100^\text{th} layer?

Note : This problem does not require a programming solution, although you may want to use a calculator for the last step!


The answer is 760874499.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

8 solutions

Arjen Vreugdenhil
Feb 11, 2018

Let A ( x , y , z ) A(x,y,z) be the number in column x x , row y y of layer z z . Then A ( x , y , z ) = ( z 1 x 1 ) ( z 1 y 1 ) . A(x,y,z) = \binom {z-1}{x-1}\binom{z-1}{y-1}. It follows then that A ( 3 , 4 , 100 ) = ( 99 2 ) ( 99 3 ) = 99 98 99 98 97 2 6 = 33 49 99 98 97 = 760 874 499 . A(3,4,100) = \binom{99}{2}\binom{99}{3} = \frac{99\cdot 98\cdot 99\cdot 98\cdot 97}{2\cdot 6} = 33\cdot 49\cdot 99\cdot 98\cdot 97 = \boxed{760\,874\,499}.


The idea for this solution comes from observing that the rule for determining the numbers is a 3D-version of the rule for Pascal's triangle.

In fact, the pyramid is the product, both geometrically and numerically, of two copies of Pascal's triangle.


Proof by induction : Suppose the statement holds true for all blocks in layer z z . Then we are told that A ( x , y , z + 1 ) = A ( x 1 , y 1 , z ) + A ( x 1 , y , z ) + A ( x , y 1 , z ) + A ( x , y , z ) ; A(x,y,z+1) = A(x-1,y-1,z) + A(x-1,y,z) + A(x,y-1,z) + A(x,y,z); with the induction assumption, A ( x , y , z + 1 ) = ( z 1 x 2 ) ( z 1 y 2 ) + ( z 1 x 1 ) ( z 1 y 2 ) + ( z 1 x 2 ) ( z 1 y 1 ) + ( z 1 x 1 ) ( z 1 y 1 ) = { ( z 1 x 2 ) + ( z 1 x 1 ) } { ( z 1 y 2 ) + ( z 1 y 1 ) } , A(x,y,z+1) = \binom{z-1}{x-2}\binom{z-1}{y-2} + \binom{z-1}{x-1}\binom{z-1}{y-2} + \binom{z-1}{x-2}\binom{z-1}{y-1} + \binom{z-1}{x-1}\binom{z-1}{y-1} \\ = \left\{\binom{z-1}{x-2} + \binom{z-1}{x-1}\right\}\left\{\binom{z-1}{y-2} + \binom{z-1}{y-1}\right\}, which with the familiar addition property of binomial coefficients becomes = ( z x 1 ) ( z y 1 ) . = \binom{z}{x-1}\binom{z}{y-1}.

Shouldn't the first line in your proof by induction be A ( x , y , z + 1 ) = A ( x 1 , y 1 , z ) + A ( x , y 1 , z ) + A ( x 1 , y , z ) + A ( x , y , z ) A(x, y, z + 1) = A(x - 1, y - 1, z) + A(x, y - 1, z) + A(x - 1, y, z) + A(x, y, z) ?

David Vreken - 3 years, 3 months ago

Log in to reply

Very well. I will fix it.

Arjen Vreugdenhil - 3 years, 3 months ago

Log in to reply

Your proof by induction is much better than mine - nicely done! (I assume that ( n k ) n \choose k when k < 0 k < 0 and k > n k > n is defined to be 0 0 .)

David Vreken - 3 years, 3 months ago

 1
 2
 3
 4
 5
 6
 7
 8
 9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
import numpy as np
def binomial_coefficients_list(n):
    """ Return a list of binomial coefficients as rows of the Pascal's
    triangle.
    """
    d = [1] * (n + 1)
    a = 1
    for k in range(1, n//2 + 1):
        a = (a * (n - k + 1))//k
        d[k] = d[n - k] = a
    return d

#-----------------------------------------------------------------------

layer = 100
row = 4
col = 3

x = binomial_coefficients_list(layer-1)
arr = np.empty(len(x)**2).reshape(len(x), len(x))

for k1,i in enumerate(x):
    for k2,j in enumerate(x):
        arr[k1,k2] = int(i*j)

print 'Row %d and Column %d in Layer %d is : %d' \
        % ( row, col, layer, int(arr[row-1,col-1]))

1
2
Row 4 and Column 3 in Layer 100 is : 760874499
For what it's worth, Row 50 and Column 50 in Layer 100 is : 2544765851052936307497981610959896795699381797787015315456

Michael Fitzgerald - 3 years, 3 months ago

Log in to reply

That's so cool!

16TUCS121 MOUYA C.P - 3 years, 3 months ago

Upvote here. Nice work Arjen!!

Michael Fitzgerald - 3 years, 3 months ago

Is it just me or is there something i'm not getting. Each block can only have 4 blocks at most touching its top. If you are adding up all the blocks on top of the blocks that are touching then the examples are wrong. example 3 should have a 5 in the center if its a summation game as it would have all 4 blocks from layer 2 in direct contact with it plus the on block from layer 1 directly over it. Maybe its just me. wish i could have posted this query independently instead of on someones post but could figure out how.

David Lynch - 3 years, 3 months ago

Log in to reply

"... every other block has the sum of all the blocks that touch its top side"

Arjen Vreugdenhil - 3 years, 3 months ago

I'd like to add that numbers on the blocks in the n-th layer are coefficients of the polynomial ( 1 + x ) n ( 1 + y ) n = i j C i j n x i y j (1+x)^n(1+y)^n = \sum_{ij} C_{ij}^n x^i y^j .

Darko Simonovic - 2 years, 10 months ago

Log in to reply

That is true; but how does it help in solving the problem?

Arjen Vreugdenhil - 2 years, 10 months ago
David Vreken
Feb 1, 2018

It can proved inductively that the block in column c c , row r r , and layer n n would have the number ( n 1 c 1 ) ( n 1 r 1 ) {n - 1 \choose c - 1}{n - 1 \choose r - 1} written on it (see proof below). Therefore, the block in column 3 3 , row 4 4 , and layer 100 100 would have the number ( 100 1 3 1 ) ( 100 1 4 1 ) = 760874499 {100 - 1 \choose 3 - 1}{100 - 1 \choose 4 - 1} = \boxed{760874499} written on it.


To prove that each block in column c c , row r r , and layer n n would have the number ( n 1 c 1 ) ( n 1 r 1 ) {n - 1 \choose c - 1}{n - 1 \choose r - 1} written on it, we must examine each type of block, namely the non-edge blocks, the left edge blocks, the back edge blocks, the right edge blocks, the front edge blocks, and the corner blocks, and show that the equation holds for the first case and for each case after it.

The first non-edge block appears on layer n = 3 n = 3 , column c = 2 c = 2 , and row r = 2 r = 2 , and is 4 4 , and ( 3 1 2 1 ) ( 3 1 2 1 ) = 4 {3 - 1 \choose 2 - 1}{3 - 1 \choose 2 - 1} = 4 . All non-edge blocks in layer n n , column c c , and row r r are the sum of the 4 4 blocks above it, which is ( n 2 c 1 ) ( n 2 r 1 ) + ( n 2 c 2 ) ( n 2 r 1 ) + ( n 2 c 1 ) ( n 2 r 2 ) + ( n 2 c 2 ) ( n 2 r 2 ) {n - 2 \choose c - 1}{n - 2 \choose r - 1} + {n - 2 \choose c - 2}{n - 2 \choose r - 1} + {n - 2 \choose c - 1}{n - 2 \choose r - 2} + {n - 2 \choose c - 2}{n - 2 \choose r - 2} , and simplifies (with some algebraic manipulation) to ( n 1 c 1 ) ( n 1 r 1 ) {n - 1 \choose c - 1}{n - 1 \choose r - 1} .

All left edge blocks are when c = 1 c = 1 , and the first one appears on layer n = 3 n = 3 , column c = 1 c = 1 , and row r = 2 r = 2 , and is 2 2 , and ( 3 1 1 1 ) ( 3 1 2 1 ) = 2 {3 - 1 \choose 1 - 1}{3 - 1 \choose 2 - 1} = 2 . All left edge blocks in layer n n , column c c , and row r r are the sum of the 2 2 blocks above it, which is ( n 2 c 1 ) ( n 2 r 1 ) + ( n 2 c 1 ) ( n 2 r 2 ) {n - 2 \choose c - 1}{n - 2 \choose r - 1} + {n - 2 \choose c - 1}{n - 2 \choose r - 2} , and also simplifies to ( n 1 c 1 ) ( n 1 r 1 ) {n - 1 \choose c - 1}{n - 1 \choose r - 1} .

All right edge blocks are when c = n c = n , and the first one appears on layer n = 3 n = 3 , column c = 3 c = 3 , and row r = 2 r = 2 , and is 2 2 , and ( 3 1 3 1 ) ( 3 1 2 1 ) = 2 {3 - 1 \choose 3 - 1}{3 - 1 \choose 2 - 1} = 2 . All right edge blocks in layer n n , column c c , and row r r are the sum of the 2 2 blocks above it, which is ( n 2 c 2 ) ( n 2 r 1 ) + ( n 2 c 2 ) ( n 2 r 2 ) {n - 2 \choose c - 2}{n - 2 \choose r - 1} + {n - 2 \choose c - 2}{n - 2 \choose r - 2} , and also simplifies to ( n 1 c 1 ) ( n 1 r 1 ) {n - 1 \choose c - 1}{n - 1 \choose r - 1} .

All back edge blocks are when r = 1 r = 1 , and the first one appears on layer n = 3 n = 3 , column c = 2 c = 2 , and row r = 1 r = 1 , and is 2 2 , and ( 3 1 2 1 ) ( 3 1 1 1 ) = 2 {3 - 1 \choose 2 - 1}{3 - 1 \choose 1 - 1} = 2 . All back edge blocks in layer n n , column c c , and row r r are the sum of the 2 2 blocks above it, which is ( n 2 c 1 ) ( n 2 r 1 ) + ( n 2 c 2 ) ( n 2 r 1 ) {n - 2 \choose c - 1}{n - 2 \choose r - 1} + {n - 2 \choose c - 2}{n - 2 \choose r - 1} , and also simplifies to ( n 1 c 1 ) ( n 1 r 1 ) {n - 1 \choose c - 1}{n - 1 \choose r - 1} .

All front edge blocks are when r = n r = n , and the first one appears on layer n = 3 n = 3 , column c = 2 c = 2 , and row r = 3 r = 3 , and is 2 2 , and ( 3 1 2 1 ) ( 3 1 3 1 ) = 2 {3 - 1 \choose 2 - 1}{3 - 1 \choose 3 - 1} = 2 . All front edge blocks in layer n n , column c c , and row r r are the sum of the 2 2 blocks above it, which is ( n 2 c 1 ) ( n 2 r 2 ) + ( n 2 c 2 ) ( n 2 r 2 ) {n - 2 \choose c - 1}{n - 2 \choose r - 2} + {n - 2 \choose c - 2}{n - 2 \choose r - 2} , and also simplifies to ( n 1 c 1 ) ( n 1 r 1 ) {n - 1 \choose c - 1}{n - 1 \choose r - 1} .

All the corner blocks are equal to the one block above it, which is always 1 1 , and for each corner case (when c = 1 c = 1 and r = 1 r = 1 , when c = 1 c = 1 and r = n r = n , when c = n c = n and r = 1 r = 1 , and when c = n c = n and r = n r = n ), the first ones appear on layer n = 2 n = 2 , and ( 2 1 1 1 ) ( 2 1 1 1 ) = 1 {2 - 1 \choose 1 - 1}{2 - 1 \choose 1 - 1} = 1 , ( 2 1 1 1 ) ( 2 1 2 1 ) = 1 {2 - 1 \choose 1 - 1}{2 - 1 \choose 2 - 1} = 1 , ( 2 1 2 1 ) ( 2 1 1 1 ) = 1 {2 - 1 \choose 2 - 1}{2 - 1 \choose 1 - 1} = 1 , and ( 2 1 2 1 ) ( 2 1 2 1 ) = 1 {2 - 1 \choose 2 - 1}{2 - 1 \choose 2 - 1} = 1 . Also, for each corner case, ( n 1 c 1 ) ( n 1 r 1 ) = 1 {n - 1 \choose c - 1}{n - 1 \choose r - 1} = 1 .

Therefore, each block in column c c , row r r , and layer n n would have the number ( n 1 c 1 ) ( n 1 r 1 ) {n - 1 \choose c - 1}{n - 1 \choose r - 1} written on it.

Nice problem and solution.

Hana Wehbi - 3 years, 3 months ago
Victor Dumbrava
Feb 12, 2018

You might notice that the first row and the first column of the n th n^{\text{th}} layer is the n th n^{\text{th}} row in Pascal's Triangle .

We can also observe that the point at coordinates ( i , j ) (i, j) on the n th n^{\text{th}} layer is ( l 1 , j ) ( l i , 1 ) (l_{1,\space j}) \cdot (l_{i,\space 1}) , whereas l l is the layer represented using matrix notation .

Therefore, a general formula for the 3 rd 3^{\text{rd}} column and the 4 th 4^{\text{th}} row must be P n ( 3 ) P n ( 4 ) P_n(3)\cdot P_n(4) , where P a ( b ) P_a(b) represents the b th b^{\text{th}} element of the a th a^{\text{th}} row in Pascal's triangle. Now we know that Pascal's triangle is the table of binomial coefficients between its row indices and its column indices, namely ( r c ) \binom{r}{c} for the r th r^{\text{th}} row and the c th c^{\text{th}} column.

That being said, we ought to find ( 100 1 4 1 ) ( 100 1 3 1 ) = 760874499 \binom{100-1}{4-1}\cdot \binom{100-1}{3-1}=\boxed{760874499} .

Extra: The sequence of numbers on the 3 rd column and 4 th row is listed in OEIS A004282 .

Lars Sandberg
Feb 13, 2018

Notice that the numbers along the n'th edge of a layer are of the form

1 x (n-1) x (n-2)/2 x ... x (n-i)/i on the i'th place from the corners (symmetrical from both sides),

n > 2; i < n.

Notice also that the elements in layer n in the i'th row and the j'th column just are the product of the i'th and j'th edge values

In layer 100 the 3rd edge element is therefore 1 x 99 x 98/2 = 4.851 and the 4th edge element is 1 x 99 x 98/2 x 97/3 = 156.849

The (3, 4)th element in layer 100 is therefore 4.851 x 156.849 = 760.874.499

Frank Petiprin
Feb 5, 2018
 1
 2
 3
 4
 5
 6
 7
 8
 9
10
11
12
13
14
15
16
17
18
**CC PROGRAM WRITTEN IN PYTHONISTA ON A IPAD PRO**
old = [0, 1, 4, 6, 4]
new = [0, 0, 0, 0, 0]
beg = 6
end = 100
for i in range(  beg, end + 1 ):
   new[1] = old[1]
   new[2] = old[2] + 1
   new[3] = old[2] + old[3]
   old[2] = new[2]
   new[4] = old[3] + old[4]
   old[3] = new[3]
   old[4] = new[4]
   print( new, i)
**CC End For Loop**
answer = new[4]*new[3]
print('layer 100 ans = row 4 times col 3',answer)
input(' end block program ')

 1
 2
 3
 4
 5
 6
 7
 8
 9
10
11
12
13
14
15
**CC Partial Program Run**
First 4 nums in row1 Layer
[1, 89, 3916, 113564] 90
[1, 90, 4005, 117480]  91
[1, 91, 4095, 121485] 92
[1, 92, 4186, 125580] 93
[1, 93, 4278, 129766] 94
[1, 94, 4371, 134044] 95
[1, 95, 4465, 138415] 96
[1, 96, 4560, 142880] 97
[1, 97, 4656, 147440] 98
[1, 98, 4753, 152096] 99
[1, 99, 4851, 156849] 100
layer 100 ans = row 4 times col 3  = 760874499
end block program 

``` Partial Layout of layer 100 [156849 * 4851 = 760874499]

000001, 99, 4851, 000000156849,

000099, ..... , ......., ......................,

004851, ....., ......., ......................,

156849, ....., 760874499, .........., `

Didn't the question say there is no need to use programming... No points to you.

Dike Mason - 3 years, 3 months ago

Log in to reply

It is not required, but not disallowed - @Frank Petiprin is allowed his points!

Dan Wheatley - 3 years, 3 months ago
For An Angel
Feb 14, 2018

The number in the 3rd column 4th row (or 4th column and 3rd row) is the product of the 3rd and 4th numbers in the 1st row. The 3rd number is 2 less than the layer number triangulated (98 x 49.5=4851). The 4th number is the sum of all the 3rd numbers in the previous layers. So (97 x 1)+(96 x 2)+(95 x 3) ... (3 x 95)+(2 x 96)+(1 x 97)=156849. The answer is 156849 x 4851=760874499

Orion Rhoades
Feb 13, 2018

For row x, column y, and layer z, it is simply ( z 1 x 1 ) {z-1 \choose x-1} ( z 1 y 1 ) {z-1 \choose y-1} When the variables are plugged in, we get \({99 \choose 2} ) ( 99 3 ) {99 \choose 3} , which equals our answer, 760874499.

Lucas Victorino
Feb 16, 2018

My solution was to have my friend go on his computer and tell me all the answers 🤣

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...